Canadian Administrative Law: The Case for Judicial Humility - Silberman Abella, Rosalie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
For decades, the Supreme Court of Canada has contemplated the appropriate standard of judicial review of decisions by administrative tribunals. The Court has grappled with the tension between the role of, and relationship between, courts and tribunals. The author, who has been both a judge and a tribunal member, argues for an attitude of humility towards these administrative bodies. With this approach, the author argues, even those most skeptical of tribunals might recognize their value as less formal, more expeditious, more expert, and binding dispute resolution mechanisms that complement—rather than detract from or compete with—courts. They may come to appreciate tribunals as the court’s institutional justice sibling, pursuing similar ends through different means.